Differentiation between bipolar disorder and major depressive disorder in adolescents: from clinical to biological biomarkers - Yang, Ruilan; Zhao, Yanmeng; Tan, Zewen; Lai, Juan; Chen, Jianshan; Zhang, Xiaofei; Sun, Jiaqi; Chen, Lei; Lu, Kangrong; Cao, Liping; Liu, Xuemei (Frontiers in Human Neuroscience, 2023)
Background: Mood disorders are very common among adolescents and include mainly bipolar disorder (BD) and major depressive disorder (MDD), with overlapping depressive symptoms that pose a significant challenge to realizing a rapid and accurate differential diagnosis in clinical practice. Misdiagnosis of BD as MDD can lead to inappropriate treatment and detrimental outcomes including poorer ultimate clinical and functional prognosis and even increased risk of suicide. Therefore, it is of great significance for clinical management to identify clinical symptoms or features and biological markers that can accurately distinguish BD from MDD. With the aid of bibliometric analysis, we explore, visualize and conclude the important directions of differential diagnostic studies of BD and MDD in adolescents. Materials and methods: A literature search was performed for studies on differential diagnostic studies of BD and MDD among adolescents in the Web of Science Core Collection database. All studies considered for this paper were published between 2004 and 2023. Bibliometric analysis and visualization were performed using the VOSviewer and CiteSpace software. Results: In total, 148 publications were retrieved. The number of publications on differential diagnostic studies of BD and MDD among adolescents has been generally increasing since 2012, with The United States being an emerging hub with a growing influence in the field. Boris Birmaher is the top author in terms of the number of publications, and Journal of Affective Disorders is the most published journal in the field. Co-occurrence analysis of keywords showed that clinical characteristics, genetic factors and neuroimaging are current research hotspots. Ultimately, we comprehensively sorted the current state of research in this area and proposed possible research directions in the future. Conclusion: This is the first-ever study of bibliometric and visual analyses of differential diagnostic studies of BD and MDD in adolescents to reveal the current research status and important directions in the field. Our research and analysis results might provide some practical sources for academic scholars and clinical practice.